2021
DOI: 10.1016/j.cnp.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of acute vestibular neuropathy through modern vestibular testing: A descriptive analysis

Abstract: Highlights Video head impulse testing and vestibular evoked myogenic potentials show that acute vestibular neuropathy is heterogeneous. Peripheral vestibular pathway vulnerability is approximately inversely correlated with its proportion of afferent fibers. Caloric testing, while useful, should no longer be considered the gold standard for diagnosing acute vestibular neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…While the former is composed of the lateral and anterior ampullary nerves and the utricular nerve, the inferior vestibular nerve is composed of the singular nerve (or posterior ampullary nerve) and the saccular nerve ( 21 ) ( Figure 4A ). IVN is considered a rare entity, with a possible prevalence of 1.3–18% among overall VN cases, depending on different inclusion criteria and available instrumental battery ( 3 , 7 , 8 , 22 25 ). Diagnosis is often challenging due to spontaneous vertical nystagmus and lack of corrective saccades on horizontal HIT, which is supposed to guide toward an acute CNS disorder ( 5 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the former is composed of the lateral and anterior ampullary nerves and the utricular nerve, the inferior vestibular nerve is composed of the singular nerve (or posterior ampullary nerve) and the saccular nerve ( 21 ) ( Figure 4A ). IVN is considered a rare entity, with a possible prevalence of 1.3–18% among overall VN cases, depending on different inclusion criteria and available instrumental battery ( 3 , 7 , 8 , 22 25 ). Diagnosis is often challenging due to spontaneous vertical nystagmus and lack of corrective saccades on horizontal HIT, which is supposed to guide toward an acute CNS disorder ( 5 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most valid etiopathogenesis theory is the reactivation of a latent herpes simplex 1(HSV-1) inhabiting the vestibular ganglion. Superior branch involvement (affecting the horizontal semicircular canal and/or anterior semicircular canal and/or utricle) is the most frequent variant 57% [ 10 ]. Video head impulse test studies in humans [ 11 ] showed that the horizontal semicircular canal (SCC) is affected more frequently than the anterior SCC whereas deficits of the utricle are less common.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only low gain but also presence of corrective saccades should count in the definition of a vHIT abnormality (20,29,30). A differential involvement of the cVEMP and oVEMP tests has also been reported in VN and MD (31)(32)(33)(34)(35)(36). In patients with VN, we found a higher abnormal rate (50%) in the oVEMP test compared to that (30%) in the cVEMP test, suggesting a higher incidence of utricular dysfunction than saccular dysfunction in VN (37), although this was not significant in this study.…”
Section: Discussionmentioning
confidence: 99%